INVESTIGATION OF WETTABILITY, ANTIBACTERIAL ACTIVITY, THERMAL INSULATION, AND MECHANICAL CHARACTERISTICS OF ELASTOMER BLEND ADHESIVES WITH HIGH-DENSITY FIBERBOARD WOOD AND ALUMINUM - Majeed, Maha; Hussein, Seenaa (Malaysian Journal of Science, 2024)
Attention has recently been given to finding alternative and sustainable raw material sources for wood and metal adhesives, such as polyvinyl alcohol (PVA), corn starch (CS), arabic gum (AG), and dextrins (D). Modifying polymer dispersion using unique substances, such as modifying reactive elastomer liquid (EL) using PVA, CS, AG, or D results in sufficiently moisture-resistant adhesive joins. In the present study, the physical characteristics of EL/blended with the natural polymers PVA, CS, AG, and D, based on high-density fiberboard (HDF) wood and aluminum (Al) adhesives and coatings, were investigated and compared to those of pure EL. The EL was blended with PVA, CS, AG, or D at a ratio of 60/40 (w/w) to form EL/blends. The chemical structures, surface and interface morphology, adhesion strengths (including shear strength and pull-off strength), surface roughness, wettings, color intensity, and thermal insulation of the prepared EL and EL/blends were investigated. A scanning electron microscopy (SEM) investigation confirmed filler dispersion and adhesion between the blends, and coated HDF wood, or Al. The developed EL/AG blend had a pull-off strength of 144±5 and 102±3 MPa and a shear strength of 771±11, and 52±3 N with HDF wood and Al substrate, respectively. The EL/PVA blend had a maximum surface roughness value 4.57 µm, and its average water contact angle (WCA) was 85.6°. A plasma jet was used to treat the surface roughness and hence the wettability of the pure EL and the EL/blends, for example, plasma treatment decreased the roughness of the EL/AG blend from 4.36 to 3.28 μm. WCA, and hence wettability, was also significantly influenced by plasma treatment, for example, plasma treatment decreased the WCA of the pure EL from 71.7±0.4° to 30.7±0.7°. The lightness value of the EL/blends was less than that of the pure EL, indicating that (the color adhesives have darkened). Similarly, the yellowness-blueness and redness-greenness values of the EL/blends were greater than those of the pure EL,( rendering the blended adhesives more reddish and bluish). The EL/AG blend was found to have a minimum thermal conductivity (of 0.27 W/m.K), indicating maximum insulation.